Answer:
(x-2)(x-12)
Step-by-step explanation:
x^2-14x+24=(x-2)(x-12)
Answer:
f(x) = –2x + 3
Step-by-step explanation:
Answer: B) 3+y+3
This can be simplified to y+6, but the current un-simplified expression has 3 terms.
======================================
Explanation:
Terms are separated by a plus sign. If you had something like 10x-5y, then you would write that as 10x+(-5y) showing that 10x and -5y are the two terms.
Choices A and C, xy and 6y respectively, have one term each. They are considered monomials. Mono = one, nomial = name.
Choice D is the product of the constant 3 and the binomial y+3. Binomials have two terms.
Only choice B has three terms, though we can simplify it down to two terms. I have a feeling your teacher doesn't want you to simplify it.
Answer:
The equation for this sequence will be 8 + 17n - 17 with n being replaced with the term number you are trying to find.
so 8 + 17(16) - 17
17 x 16= 272
8 + 272= 280
280- 17= 263
Thus, the 16th term will be 263.
Answer: See attached image
Step-by-step explanation: